DEVELOPMENT OF THE TEACHER'S PROFESSIONAL COMPETENCE AS A FACTOR OF IMPROVING THE QUALITY OF VOCATIONAL HIGHER EDUCATION (Innovative professional education, 2023)
In ensuring quality results of professional training of future specialists, a special role belongs to the teacher, his professional competence, which combines professional knowledge, the ability of a highly qualified specialist in a certain field and mastery ofpedagogical activity. Taking this into account, the principles and modern forms and types of development of professional competence of teachers of vocational of higher education institutions.
Keywords: professional competence, development of professional competences, advanced training